End Users’ Perception on Public Wifi System – A Study Conducted In Kuala Lumpur, Malaysia - Govindaraju, Vimala; Kunachagaran, Kamalakannan; Ramakrishnan, Suresh; Hishan, Sanil S. (American Scientific Publishers, 2017)
The number of active internet users in Malaysia has now exceeded 20.1 million; with 16.8 million being active on social media. The Internet age began in Malaysia in the year 1995. Since the introduction of internet in the year 1995 it developed rapidly over the years. The demand for the free public wifi has increased drastically. The main objective of this study is to analyse in perception of the end-users of public wifi towards the public wifi service currently available in public places in the Kuala Lumpur city of Malaysia. The study also analyses the preferences of the customers on the advertisement streaming. The study used the quantitative research method. The data was collected using an online survey and the respondent included the public wifi users in Kuala Lumpur. The market survey has clearly shown that the end users are not willing to pay for the public wifi. However the end users have indicated that they may agree to have advertisement streaming if they get free wifi. As per the correlation matrix the age has a factor in the usage of internet. Mostly public wifi is used in the Smartphone, moreover the Smartphone users are one of the major targets for the end users. Hence the survey clearly points that if the wifi providers can provide a fast, secure and free wifi they can be successful in encouraging the users to use the free public wifi.